2008
DOI: 10.1017/s1049023x00005641
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Chlorine Intoxications in Swimming Pools: The Challenge of Pediatric Mass Toxicological Events

Abstract: Abbreviations: BLS = basic life support EMS = emergency medical servicesAbstract Introduction: The classical doctrine of mass toxicological events provides general guidelines for the management of a wide range of "chemical" events. The guidelines include provisions for the: (1) protection of medical staff with personal protective equipment; (2) simple triage of casualties; (3) airway protection and early intubation; (4) undressing and decontamination at the hospital gates; and (5) medical treatment with antido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…43,44 The main fundamentals of dealing with masstoxicological events include involved staff protection, proper decontamination of victims, use of water for decontamination at the assigned areas near the emergency, proper triage, patients care at one location, and review by the toxicologist. 23 The toxicologist, nursing, allied specialist's notes, and related hospital charts studied for overall handling of the incidence showed that this study met all above-mentioned fundamentals for dealing with toxicological events; however, there were some gaps found during the evaluation of the incidence handling. The main gaps are the contaminated fluid runoff facility is not available.…”
Section: Symptomsmentioning
confidence: 78%
See 1 more Smart Citation
“…43,44 The main fundamentals of dealing with masstoxicological events include involved staff protection, proper decontamination of victims, use of water for decontamination at the assigned areas near the emergency, proper triage, patients care at one location, and review by the toxicologist. 23 The toxicologist, nursing, allied specialist's notes, and related hospital charts studied for overall handling of the incidence showed that this study met all above-mentioned fundamentals for dealing with toxicological events; however, there were some gaps found during the evaluation of the incidence handling. The main gaps are the contaminated fluid runoff facility is not available.…”
Section: Symptomsmentioning
confidence: 78%
“…14 The rate of admission (40%) is higher in this study as compared to the study done by Mohan, et al (18.7%) and is almost similar to the study done by Lehavi, et al (50%). 14,23 Scene safety is essential in cases of chlorine gas incidents. Level A or B PPE is advised in large-scale industrial or warfare incidents.…”
Section: Symptomsmentioning
confidence: 99%
“…A systematic review compared different available protocols of standardized reporting [14] and we chose this protocol because it was developed to report real incidents, has a practical approach, is freely available, has been published [1,15,16] and has been used previously [10,17,18]. Other protocols are more extensive but less practical, such as the Utstein template [19], the DISAST-CIR, a protocol used by the Israeli Defense Force Home Front and Ministry of Health [20][21][22][23][24][25][26][27][28] and two unused protocols [29,30]. None of these protocols have been tested on Internal and external validity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Most are the result of some form of direct alveolar injury. These include the inhalation of toxic gases such as chlorine [1,2], direct trauma to the chest resulting in a pulmonary contusion [3–5] and re-expansion injury following a pneumothorax or other causes of lung deflation [57]. Reperfusion injury may also produce pulmonary edema.…”
Section: Noncardiogenic Pulmonary Edemamentioning
confidence: 99%